Disparity in Religious Court Decisions in Divorce Cases Due to Apostasy: Normative Analysis and Legal Construction - Rosyid Arifin; Mega Dewi Ambarwati (Civiliza Publishing, 2026)
This study aims to analyze the disparity of Religious Court decisions in divorce cases caused by apostasy and to formulate an appropriate legal construction for such cases. This research employs normative legal research using statutory, conceptual, and case approaches. The analysis focuses on three Religious Court decisions, namely Decision of the Bandung Religious Court No. 0166/Pdt.G/2017/PA.Bdg, Decision of the Palu Religious Court No. 0249/Pdt.G/2016/PA.Pal, and Decision of the Bandung Religious Court No. 147/Pdt.G/2012/PA.Bdg. Data were collected through document study of primary and secondary legal materials and analyzed qualitatively through inventory, classification, and systematization stages. The findings reveal a disparity in judicial reasoning regarding divorce due to apostasy. Some judges consider apostasy as the primary legal ground for divorce through fasakh, while others base their decisions on continuous disputes and marital disharmony resulting from apostasy. This disparity indicates inconsistency in the application of Article 116 letter (h) of the Compilation of Islamic Law, which requires apostasy to cause marital discord. Therefore, this study recommends a legal construction that recognizes apostasy as an independent ground for divorce without the necessity of linking it to continuous disputes, in order to ensure legal certainty and uniformity of decisions within the Religious Court system.